Preparing for Pediatrics: Experiential Learning Helps Medical Students Prepare for Their Clinical Placement - Sullivan, Clare; Condron, Claire; Mulhall, Claire; Almulla, Mohammad; Kelly, Maria; O'Leary, Daire; Eppich, Walter (Frontiers in Pediatrics, 2022)
Despite the importance of effective communication skills in pediatrics, clinical placements may inadequately prepare undergraduate students to communicate with children. The integration of non-clinical interactions with healthy children within a pediatric curriculum has the potential to enhance learning. We designed and implemented a novel course involving experiential learning, including video-recorded consultations with simulated parents (SPs), team-based scenarios with a pediatric mannequin, interactions with healthy children through a pre-school visit and medical student led health workshops for primary school children. Medical students at the RCSI University of Medicine and Health Sciences took part in the course. We used a mixed methods approach to assess the impact of the course. We investigated medical students' perspectives through a pre- and post-intervention questionnaire and post-intervention focus group discussions (FGDs). We assessed participating children's health literacy at the start of the course. 144/279 (51.6%) of the fourth year medical student cohort on their pediatric rotation, consented to participate in the study. All 144 (100%) of consenting students completed the pre-intervention questionnaire. 59/144 (40.1%) of consenting students completed the post-intervention questionnaire. Results showed a statistically significant improvement in ratings (p < 0.05) for items related to managing a confrontational situation involving family members, completing a psychosocial assessment with an adolescent and effectiveness using evidence-based medicine (EBM) when motivating patients. There was a statistically significant decrease in how students rated their comfort at using EBM when motivating patients. Four themes relating to how students experienced the intervention were identified from eight FGDs (n = 35 students): Shaping Student Learning; Supporting Student Learning; Developing New Skills and Feeling More Prepared. 39/49 (79.6%) children completed a health literacy assessment. All questions had a high percentage of positive responses. Question 7, understanding your doctor, had the highest proportion of negative responses (27%). Ours is one of the first studies to design an educational intervention to enhance pediatrics teaching by combining interactions with healthy children outside of a clinical setting with more traditional simulation-based approaches. We conclude that this type of intervention supports students' learning of pediatric communication skills and enhances students' perceived preparation for clinical placement.